The Analysis of Fundamental Factors Affecting Company Stock Prices (Case Studies of Companies Listed on the Indonesia Stock Exchange and Incorporated in the LQ45 Index) - Anggoro Panji Nugroho; Purwito Kesdu A.C.; Siti Fatonah; Nani Irma Susanti (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to determine empirically the effect of Price Earning Ratio (PER), Price to Book Value (PBV), Dividend per Share (DPS), Earning Per Share (EPS), Debt to Equity Ratio (DER)¸ Return On Equity (ROE), Return On Assets (ROA) and Net Profit Margin (NPM) on LQ45 company stock prices for the period 2010 – 2019. In this study stock prices are used as a dependent variable, whereas PER, PBV, DPS, EPS, DER, ROE, ROA and NPM are used as independent variables. The analytical tools used are multiple linear regression with the classic assumption test, t test, F test and the coefficient of determination test. The results of this study are PER, PBV and EPS have positive and significant effects on stock prices. ROE has a negative and significant effect on stock prices. DPS, ROA and NPM have positive and insignificant effects on stock prices. DER has a negative and insignificant effect on stock prices. The variable that has the most significant effect on stock prices is EPS. The implications of this research are that companies need to improve their performance through effective and efficient corporate financial management, increase creativity and innovation in producing new products and increasing effective marketing. For investors, EPS can be used as the main reference when conducting stock investment analysis.